Digital Media and Public Access to Educational and Political Information in Pangandaran in the Digital Age - Eni Maryani; Subekti Wirabhuana Priyadharma; Ilham Gemiharto (Ikatan Sarjana Komunikasi Indonesia, 2022)
This study discusses the use of digital media and the public’s access to information in the fields of education and politics in Pangandaran Regency, West Java. In regards to assumptions of the Social Constructionism Theory (SCOT), people’s understandings about the presence of technology in their life depend on how they interpret and treat the technology. As to the assumptions related to the public sphere, the potential for digital media to serve as a public sphere could also be questioned. This research uses a case study conducted by applying several data collection techniques, namely; in-depth interviews, observation and documentation studies. This study found that the high use of digital media in Pangandaran is not only the result of easy access but also people's perspectives of technology. Digital media can be an alternative to find educational information. However, there is still a lack of information which is needed very much by the public about educational scholarships and studies at universities. Meanwhile, political information is limited due to a lack of effort to disseminate government programs that are directly related to or will directly benefit the public. Based on these findings, it can be concluded that digital media has the potential to become a public sphere with a very limited function, namely a sphere where public interests can be discussed and citizens’ awareness of and participation in education and politics can be increased. In addition, the use of digital media can only be increased if there is awareness among individuals or institutions to utilize digital media so that the quality of digital literacy and political will possessed by all parties including the public, government and members of the Pangandaran Regency Regional House of Representatives will improve accordingly.